FAKTOR YANG MEMPENGARUHI MATURITAS MANAJEMEN RISIKO ORGANISASI DI INDONESIA - Franciskus Antonius Alijoyo; Yusuf Munawar (Center for Economic Studies Universitas Katolik Parahyangan, 2019)
Risk management maturity (RMM) is often used as an indicator to show the effectiveness of the organization’s risk management implementation. This paper discusses the factors that affect the achievement of the level of maturity in the application of risk management in organizations. Data obtained through a survey involving 55 respondents who are practitioners of risk management and processed using contingency table analysis techniques. Based on the results of data processing, the aspects that support the maturity level of the organization’s risk management are related to a clear governance structure, guidelines and procedures, leadership’s commitment and periodic reviews, human resources who have competence in the field of risk management to create culture of risk awareness, integrated management and performance management system, as well as organizational resilience and sustainability management systems.